Effect of Different Chemicals and PGR on Flower Induction and Physicochemical Properties of Litchi cv. Bombai Grown in New Alluvial Zone of West Bengal - Das, Kaushik; Dutta, Pallab (International Journal of Bio-resource and Stress Management, 2022)
The present investigation was carried out at Regional Research Station, New Alluvial Zone, Bidhan Chandra Krishi Viswavidyalaya, Gayeshpur, Nadia, West Bengal, India to study the effect of different chemicals and plant growth regulators on flowering induction and physico-chemical properties of Litchi cv. Bombai for three consecutive years during September 2014 to July 2017. Nine treatments with 3 replications was chosen and laid out in Randomized Block Design using DMRT for the experiment. All the plants were 12 years of age uniform in growth and healthy spaced at 10 m apart. Results from the experiment revealed that application of different chemicals and PGR significantly improved the flowering and physicochemical properties of litchi. Among the different treatments in study, application of K2HPO4 @ 1%+KNO3 @ 1% in (T6) showed highest flowering characters in terms of flowering shoot (56.17%), sex ratio (3.62), fruits panicle-1 at harvest (26.34) and lowest fruit drop panicle-1 (14.00) followed by T7 (KH2PO4 @ 1%+KNO3 @ 1%). T6 treatment also showed maximum fruit weight (21.78 g), fruit length (3.84 cm), aril weight (15.88 g) and yield (72.34 kg plant-1). TSS (16.80°B), total sugar (13.63%), ascorbic acid (42.55 mg 100 g-1), TSS: acid ratio (57.40) and anthocyanin content (46.14 mg 100 g-1) of fruit was also found highest in T6 (K2HPO4 @ 1%+KNO3 @ 1%) followed by T7 (KH2PO4 @ 1%+KNO3 @ 1%) while the lowest in control. Thus, from the different treatment under study T6 proved to be most effective followed by T7 in improving the flower induction, yield and quality of litchi cv. Bombai.